IMPLEMENTACIÓN CONTABLE EN LA EMPRESA ́ ́CARLOS GRANDA ELECTRODOMÉSTICOS & MÁS /SOLUCIONES DIGITALES ́ ́ DE LA CIUDAD DE LOJA, PERÍODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2020 - Abrigo Reinoso, Jennifer Thalía (2021)
The present research work entitled ; ACCOUNTING IMPLEMENTATION IN THE COMPANY ''CARLOS GRANDA ELECTRODOMÉSTICOS & MÁS /SOLUCIONES DIGITALES'' OF THE CITY OF LOJA, PERIOD FROM SEPTEMBER 1 TO DECEMBER 31, 2020, has the purpose of implementing commercial and service accounting in order to provide the owner with accurate, efficient and orderly information of the economic activities of the company, through the preparation of financial statements and indicators, which will allow a correct decision making. In order to comply with the proposed objectives, it was necessary to apply methods to obtain the necessary information that would allow the creation of a plan and manual of accounts according to the nature of the company and at the same time its classification, codification and respective description of the accounts of assets, liabilities and equity, and at the same time the initial inventory was made with its respective organization of the goods, values and obligations. Based on the data obtained, the auxiliary books of purchases, sales, accounts receivable, accounts payable, roles of payments and provisions were designed, which simplified the information at the time of its accounting registration in the daily book, in addition to the general ledger, trial balance, work sheet, adjustments until obtaining the financial statements, which reflected a net profit for the fiscal year of $ 235.48 from September to December 2020. To expand the financial information of the business with the data obtained in the financial statements, the application of the indicators that allowed measuring the liquidity was carried out, presenting a solvency index of $5.74, thus demonstrating the capacity that the business has to face the short-term obligations; with respect to the activity indicator, a turnover of 0.82 times was obtained during the analyzed process; indebtedness presented an index of 16.13% demonstrating the participation of the obligations over the assets is low; and with respect to the profitability index, a net profit margin of 0.72% was 5 obtained, representing a low value of the profitability index. 0,61% representing a low value of profit generated in the fiscal year compared to the investment and expenses established. With the accounting implementation and application of the financial indicators, it was possible to establish an order and control in its daily operations through the accounting records, in addition to knowing the economic reality of the company, which will serve as a basis for making decisions to improve the shortcomings and generate more profit and benefits.